-2(9x-9)+7x=4(x+9)

Simple and best practice solution for -2(9x-9)+7x=4(x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(9x-9)+7x=4(x+9) equation:



-2(9x-9)+7x=4(x+9)
We move all terms to the left:
-2(9x-9)+7x-(4(x+9))=0
We add all the numbers together, and all the variables
7x-2(9x-9)-(4(x+9))=0
We multiply parentheses
7x-18x-(4(x+9))+18=0
We calculate terms in parentheses: -(4(x+9)), so:
4(x+9)
We multiply parentheses
4x+36
Back to the equation:
-(4x+36)
We add all the numbers together, and all the variables
-11x-(4x+36)+18=0
We get rid of parentheses
-11x-4x-36+18=0
We add all the numbers together, and all the variables
-15x-18=0
We move all terms containing x to the left, all other terms to the right
-15x=18
x=18/-15
x=-1+1/5

See similar equations:

| x2+6x−18=0 | | 15-5=1/2n | | -3+11y+7=14+15y-18 | | 18-6k=6(1-3k) | | 6n+9=-3n−21−66n+9=-3n-21-6 | | 1/2(6x-4)=3x+1 | | 24/5z=4/z-1 | | (5x+3)x(2+5x)=0 | | 2f-6-5=-22 | | 1/10n+1/10=8 | | X-2=-(x-2) | | x+9/2=8 | | 8n-8=-96 | | 0.4y+0.8=0.3-0.1y | | 1r/15+1=106 | | 8x^+7x-32=0 | | -3(x-5)=2(4x-3) | | 5x=9(x-1) | | |3x+2|-2=6 | | 3x-1=8x-24 | | 60+42.25x=25+49.95x | | 5x-3=8× | | -3(k-7)=5k-19 | | 3x-5(x-5)=-4+3x+19 | | (4g+2)4=6(5-3g) | | 4x^2+38x+96=0 | | 17-2x=-5x+17 | | 2(4x+11)=10 | | 9-(n)/4=15 | | 3(x-4)=-2(x-16) | | 60+42.25x=25+49.95 | | -2(18-3y=7y+2y |

Equations solver categories